Trilateration Method for Estimating Location in RSSI-Based Indoor Positioning System Using Zigbee Protocol - Herryawan Pujiharsono; Duwi Utami; Rafina Destiarti Ainul (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2020)
Wireless network technology that is used today is developing rapidly because of the increase needed for location information of an object with high accuracy. Global Positioning System (GPS) is a technology to estimate the current location. Unfortunately, GPS has a lack of accuracy around 10 meters when used indoors. Therefore, it began to be developed with the concept of an indoor positioning system. This is a technology used to estimate the location of objects in a building by utilizing WSN (Wireless Sensor Network). The purpose of this study is to estimate the location of the unknown nodes in the lecturer room as objects and obtain the accuracy of the system being tested. The positioning process is based on the received signal strength (RSSI) on the unknown node using the ZigBee module. The trilateration method is used to estimate the unknown nodes located at the observation area based on the signal strength received at the time of testing. The result shows that the path loss coefficient value at the observation area was 0.9836 and the Mean Square Error of the test was 1.54 meters, which implies that the system can be a solution to the indoor GPS problem.